Lidocaine supplementation in clove-oil and 2-phenoxyethanol anesthesia for gilthead seabream (Sparus aurata) - Tchobanov, Carolina F. (2024)
Animal welfare and reducing stress during procedures are key objectives for success in animal production. Anesthesia has been used for procedures to reduce animal stress and its negative impact on welfare. This study aimed first to refine the concentrations of the anesthetic clove-oil (CO) and lidocaine (L) in gilthead seabream (Sparus aurata) juveniles (56.0 ± 15.09 g) and then combine clove-oil and 2-phenoxyethanol (2PHE) with the refined concentration of lidocaine. The concentrations of clove-oil (30, 45, and 60 mg L− 1), and the concentrations of lidocaine (2.5, 5, and 7.5 mg L− 1), were evaluated in the refinement trial. Based on these results, a second trial was performed with 45 mg L− 1 CO or 0.4 mL L− 1 2PHE as anesthetics alone or combined with 2.5 mg L− 1 of lidocaine. Results from this work showed an improvement in induction times for 2-phenoxyethanol when lidocaine was added (2PHE 179.53 ± 63.21 s; 2PHE + L 130.65 ± 40.16 s). Recovery time also showed a reduction for clove-oil when lidocaine was used (CO 349.90 ± 123.69 s; CO + L 250.11 ± 51.99 s). The use of lidocaine showed better results, reducing lactate and histological progressive alterations. Lidocaine showed stress-induced oxidative alterations when it was combined with 2-phenoxyethanol. Lidocaine exposure increased ALT, AST, histological regressive alterations for both anesthetics, and gene expression of hsp70 in the gills when clove-oil was used. Further studies are necessary to comprehend the synergistic effects of lidocaine when combined with synthetic and natural anesthetics and to discern potential acute or chronic toxic responses in fish. These insights will be crucial for refining anesthesia protocols and ensuring the well-being of aquatic species in aquaculture practices and research settings.